2023
DOI: 10.1002/aic.18008
|View full text |Cite
|
Sign up to set email alerts
|

A Benders decomposition framework for the optimization of disjunctive superstructures with ordered discrete decisions

Abstract: This study introduces the logic‐based discrete‐Benders decomposition (LD‐BD) for Generalized Disjunctive Programming (GDP) superstructure problems with ordered Boolean variables. The key idea is to obtain Benders cuts that use neighborhood information of a reformulated version of Boolean variables. These Benders cuts are iteratively refined, which guarantees convergence to a local optimum. A mathematical case study, the optimization of a network with Continuous Stirred‐Tank Reactors (CSTRs) in series, and a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…For future work, we aim to extend the D‐SDA framework for the integration of design and NMPC‐based control for more complex systems, for example, reactive distillation columns. An improved search strategy based on a GBD 38 will be incorporated into the present framework to avoid the use of auxiliary function in the algorithm (e.g., ΨP) and to reduce the computational cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For future work, we aim to extend the D‐SDA framework for the integration of design and NMPC‐based control for more complex systems, for example, reactive distillation columns. An improved search strategy based on a GBD 38 will be incorporated into the present framework to avoid the use of auxiliary function in the algorithm (e.g., ΨP) and to reduce the computational cost.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we aim to extend the D-SDA framework for the integration of design and NMPC-based control for more complex systems, for example, reactive distillation columns. An improved search strategy based on a GBD38 will be incorporated into the present framework to avoid the use of auxiliary function in the algorithm (e.g., Ψ P ) and to reduce the computational cost.AUTHOR CONTRIBUTIONSOscar Palma-Flores: conceptualization (equal); formal analysis (lead); investigation (equal); methodology (equal); validation (lead); visualization (lead); writingoriginal draft (lead). Luis A. Ricardez-Sandoval: conceptualization (lead); formal analysis (lead); funding acquisition (equal); investigation (lead); methodology (lead); project administration (equal); supervision (lead); validation (equal); writingreview and editing (lead).…”
mentioning
confidence: 99%
“…The ordered discrete decisions may not appear explicitly in the formulation; thus, a reformulation of the problem is usually required . In general, ordered discrete decisions may appear as explicit integer variables or as groups of binary/Boolean variables Y i defined over ordered sets (i.e., i ∈ Ordered set) plus an assignment constraint (i.e., exactly k Y i are 1/True) . In this case, there is a mixture of both: batching variables n i,j , ∀( i , j ) ∈ IJ × (eq ) are explicitly ordered discrete decisions, whereas Boolean variables Y τ i,j ,i,j , ∀( i , j ) ∈ IJ × are ordered discrete decisions with respect to index τ i,j ∈ Τ i,j (eq ), where Τ i,j can be regarded as an ordered set.…”
Section: Mathematical Frameworkmentioning
confidence: 99%
“…These special variables have only been studied in the context of optimal process design and simultaneous design and control. 27,28 It has been shown that general-purpose MINLP solvers are unable to effectively capture these ordered structures in their optimization procedures, leading to suboptimal solutions and lengthy computational times. To overcome this limitation, the Discrete-Steepest Descent Algorithm (D-SDA) was developed as a specialized decomposition strategy to effectively optimize ordered discrete decisions in MINLP superstructure design problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation